Breathing poetry: La poesía de Jane Duran. - Abad García, Pilar (Estudios Ingleses de la Universidad Complutense, 2001)
This article aims at making a contribution in support of authorial and critical stances favourable not only to the publication and reading of contemporary English poetry made by women (France 1993; Dunmore 1995) but, above all, favourable to the discussion of such poetry as the only means of access to the literary canon (Dooley, 1997). Consequently, the article makes a detailed reading and discussion, both notional and formal, of the poetic production so far of one of these women poets, Jane Duran, a poet of thematic gravity and variety, of strange lexical precision and phono-syntactic and semantic richness, who starts to be widely acknowledged (Forward Poetry Prize for Best Collection of 1995) in the thriving and brilliant panorama of contemporary English poetry written by women. I. INTRODUCCIÓN En la